`INVENTARISASI JENIS-JENIS SERANGGA ORDO ORTHOPTERA PADA TANAMAN JAGUNG DI DESA KESIMAN-DENPASAR - Diah Purnama Sari, I Gusti Putu; Suartini, Ni Made; Muksin, I Ketut (SIMBIOSIS, 2018)
In Indonesian national economics, maize is a second food source after rice. The production of maize in some aspect is affected by the presence of insect particularly Orthopteran Order. The information of advantage and disadvantage of insects is useful for farmers. This research aimed to determine the species of Orthopteran and it is role to maize plant in the Village Kesiman, Denpasar. This research was conducted from December 2015 to February 2016. Insect was collected using sweeping net accordingly in each plot of maize plants. The plot was square form with the size of 10 m x 25 m. The sample was collected from the maize plant in the Ve phase until physiological maturation phase. in each phase, from 07.00 am until 10.00 am Bali time. Sample was collected for 15 minutes per plot and repeated three times. The insects collected was identified, and the insect density was predicted following Krebs (1989). As many as 242 individual insect which belong to Orthopteran Order was collected. Those belong to 8 families and 25 species. The species were Atractomorpha sp., Orchelimum sp., Phlaeoba sp., Gastrimargus sp., Urnisiella sp., Metaleptea brevicornis , Xenocatantops sp., Scudderia sp., Calolampra sp., Eritettix sp., Platyzoteria sp., Conocephalus strictus , Morabine sp., Acrida sp., Tenodera sp., Stagmomantis sp., Blattela sp., Periplaneta sp., Tettigidea lateralis , Mantis sp., Gryllus sp., and Anaxipha exigua , Tettigidea sp. 2, Tettigidea sp. 1, and unidentified (species x).  Families that act as omnivores are Family Blattidae and Grillidae, families that act as herbivores are Pyrgomorphidae, Acrididae, Tettigonidae, Eumastacidae, and Tetrigidae, while families that act as predators are Mantidae. Keyword : m aize, o rthopteran, insect species, insect role.